Methane and Carbon Dioxide Hydrate Formation in the Presence of Metal-Based Fluid - Nashed, O. (MDPI, 2022)
Hydrate-based technology has yet to find its way to commercial applications due to several issues, including formation conditions and slow kinetics. Several solid particles were introduced to speed up hydrate formation. However, these solid compounds have given contradictory results. This study investigated the effect of high thermal conductive metallic nanofluids of silver (Ag) and copper (Cu) on CH4 and CO2 hydrates. The solid particles were suspended in a 0.03 wt SDS aqueous solution, and the results were compared with the 0.03 wt SDS and deionized water samples. A stirred tank batch reactor was used to conduct the thermodynamic and kinetic experiments. The thermodynamic study revealed that 0.1 wt of solid particles do not shift the equilibrium curve significantly. The kinetic evaluation, including induction time, the initial rate of gas consumption, half-completion time, t50 and semi-completion time, t95, gas uptake, and storage capacity, have been studied. The results show that the Ag and Cu promote CH4 hydrates while they inhibit or do not significantly influence the CO2 hydrates formation. A predictive correlation was introduced to get the apparent rate constant of hydrate formation in the presence of metal-based fluid at the concentrations range of 0.005â0.1 wt. Â© 2022 by the authors.